Bazaars and Trade Integration in CAREC Countries - World Bank (Washington, DC, 2014)
This paper based on survey work as well as an examination of trade statistics is the first to have studied the economic and trade effects of bazaars in central Asia in a detailed way. It presents a wealth of information and statistics relating to critical income generating activities and seeks to uncover the vital role played by bazaars in supporting economic growth. The analysis conducted in this work is of policy interest: rather than treating bazaars as unorganized and undesirable features of a modern market economy, national authorities should foster the development of bazaars in view of the growth, employment-generation and poverty-fighting characteristics of the operations of bazaars. Indeed, without well-functioning bazaars, the cost of trade would be considerably greater, the prices of goods higher and availability more restricted, trade volumes considerably lower, and the powerful welfare-raising effects from re-exports (in which bazaars play a critical role) as well as trade itself would be greatly muted. The populations would be much the poorer. The remainder of this report is organized as follows: section one provides birds' eye-view of networks of bazaars: their structure and weight in local economies as well as their involvement in domestic and foreign trade activities. Section two provides estimates of trade mediated by bazaars based on both mirror, i.e., Central Asian's (CA's) trading partners' trade statistics and national statistics of Kazakhstan and Kyrgyzstan. Section three presents conclusions and outlines policy implications of empirical findings.